The Linguostylistic Studies of Nadiia Babych (Linguostylistic Studies, 2018)
In recent years linguists have become increasingly interested in the linguistic-stylistic studies of the scholars, who contributed to the formation of stylistics as a science and initiated new trends in stylistics and who themselves are an example of the linguistic culture and linguistic behavior. One of them is Nadiia Babych.The aim of the article is to analyze the scientific works written by Nadiia Babych in the field of linguistic stylistics, to clarify the issues and themes of her studies and to outline the prospects for further research of the author's literary language personality. The tasks of the study are: 1) analysis of the scientific and scientific-methodical works by N. Babych devoted to the study of stylistic differentiation of language, elucidation of modern Ukrainian literary language style features and their description; 2) reviewing the works of the linguist with a focus on the study of the levels of the language system various elements additional stylistic meanings; 3) clarifying the importance of N. Babich’s works regarding individual author's language style in the context of linguistic and stylistic research; 4) outlining further research issues of the linguistic image of N. Babich as a scientist in modern linguopersonology.Nadiia Babych owns many works on theoretical issues of stylistics namely its place among other philological sciences, the notion of style, a substyle and a genre, the practical aspects like stylistic differentiation of lexical and grammatical means of language, peculiarities of their use depending on the content of the text, emotional and expressive color, author's style, which is a significant contribution to the formation and development of the Ukrainian linguistic stylistics.General characteristics of a scientist’s thinking and her language image allow distinguishing the specific features of the individual style. The scientific text of Nadiia Babych is primarily marked by the valid arguments, bright quotes, adequate linguistic norms of modern language, the predominance of the genuine Ukrainian words over foreign ones.The characteristic features that determine the linguistic individuality of Nadiia Babych comprise figurative and emotional discourse, a harmonious balance in the use of terminology and a commonly used vocabulary, avoidance of categorical judgments, variety of parenthetical and exclamatory sentences, rhetorical questions, availability of functional guidance to comprehend a text.Analysis of the linguistic, stylistic, scientific, and methodological works by Nadiia Babych has revealed a high level of understanding of the theoretical and practical issues, related both to the theory of styles and to functioning of individual linguistic units of different levels, a variety of the subjects of the research issues, the originality in scientific thought and extraordinary skills of the language creativity. Further studies of Nadiia Babych's linguistic personality of a scientist and the creation of a linguistic portrait of the scholar, who is an exemplar of the Ukrainian elitist speech culture, are perspective and promising.
Keywords: linguistic style; linguopersonology; style; linguistic personality; individual style; linguistic thinking; language creation